Ocular and vision defects in preschool children. Issue 4 (April 1993) - Stayte, M; Reeves, B; Wortham, C
Abstract : Ocular and/or vision defects are one of the commonest reasons for the referral of young children to hospital. In a survey of a birth cohort in one health district, 7.1% of children were diagnosed as having such defects by their fifth birthday; 2.1% were detected before the age of 2 years, and 5.1% between 2 and 5 years. Up to the age of 2 years, low birthweight children and those who require postnatal special care had a higher risk of having an ocular or vision defect diagnosed and were more likely to have serious visual impairment than other children. In contrast, between the ages of 2 and 5 years of age these high risk children showed no continuing increased risk of having a defect diagnosed, nor did they show any differences in the severity or type of vision defects compared with other children. Averaged over the years studied, the incidence of defects presenting to specialist eye clinics among all 2-5 year olds was 1.7%, higher than the 1.1% found for 0-2 year olds. This increase consisted primarily of children with refractive errors only.